COMPARATIVE ANALYSIS OF RISK AND RETURN ON INDONESIAN ISLAMIC STOCK INDEX IN DIFFERENT ECONOMIC CONDITIONS - Deni Pandu Nugraha (Universitas Muhammadiyah Kalimantan Timur, 2021)
This study aims to analyze the differences in risk and rate of return on Islamic stocks during the economic crisis, when the economy is stable, and during the pandemic-covid. The sample used is the Indonesian Islamic stock index JII30 from 2018-2020. The data analysis used was a different test (T-test). The test variable uses stock returns and risk as proxied by Value at Risk (VaR). The results indicate there is no significant difference in the return and risk of stock index JII30 between economic crisis conditions and when economic conditions are stable. However, there is a significant difference between the JII30 stock index when the economy is stable and during the pandemic-covid, also there were significant differences in return and risk in the JII30 Index between the economic crisis (2018) and the pandemic's economic conditions (2020).